The evolution of financing structure in U.S. startups - Carmen Cotei; Joseph Farhat (The Journal of Entrepreneurial Finance (JEF), 2017)
In this article we examine how startup businesses finance their operations over time. We employ the Latent growth modeling technique to test the financial growth cycle theory developed by Berger and Udell (1998). The data used in this study is the Kauffman Firm Survey, the largest longitudinal data set comprised of a random sample of U.S. startups launched in 2004 and surveyed annually through 2011. Consistent with the predictions of financial growth cycle theory, in the startup stage, entrepreneurs rely on initial insider capital sources such as personal savings, financing offered by friends and family, quasi-equity, and personal debt. Over time, as businesses become less opaque, the proportion of business debt and trade credit financing in total capital injection volume increases significantly. Businesses with high R&D activity and those that possess intellectual property rights finance their operations predominantly with equity - particularly external equity raised from angels and venture capitalists, and business debt - particularly bank loans and credit lines. Owner's education and race have a significant impact on the type of capital injections over the business life cycle. Highly educated owners choose to inject lower proportions of personal debt and trade financing, whereas white owners inject lower proportions of personal equity and rely more on trade financing.
Keywords: C83; G32; M13; O31; O32; 650; startups; financing structure; financial growth cycle theory; R&D intensity; intellectual property rights; survey methodology